Biased assessment of gestational age at birth when obstetric gestation is known. Issue 1 (January 1993) - Gagliardi, L; Brambilla, C; Bruno, R; Martinelli, S; Console, V
Abstract : The gestational age of 302 neonates whose obstetric gestational age was known was assessed at birth using the Dubowitz method; it was obtained from Dubowitz score both graphically from a nomogram and by calculation from the corresponding equation. The values obtained graphically differed to a lesser extent from the obstetric gestational age than did the gestation derived algebraically. With infants small for gestational age (SGA) the difference between the methods was smaller and not significant. It is concluded that the concurrent knowledge of obstetric gestational age introduced a bias in the graphic step; this did not happen in SGA infants probably because in these cases the available information is sometimes less certain. These data demonstrate that even simple procedures are influenced by concurrent information; as a philosophical point about the interpretation of data in general, this study provides an empirical example of the 'theory-ladenness of facts' in medicine.